Raman quantum memory with built-in suppression of four-wave-mixing noise - Thomas, SE; Hird, TM; Munns, J; Brecht, B; Saunders, D; Nunn, J; Walmsley, IA; Ledingham, PM (American Physical Society, 2019)
Quantum memories are essential for large-scale quantum information networks. Along with high efficiency, storage lifetime, and optical bandwidth, it is critical that the memory adds negligible noise to the recalled signal. A common source of noise in optical quantum memories is spontaneous four-wave mixing. We develop and implement a technically simple scheme to suppress this noise mechanism by means of quantum interference. Using this scheme with a Raman memory in warm atomic vapor, we demonstrate over an order of magnitude improvement in noise performance. Furthermore we demonstrate a method to quantify the remaining noise contributions and present a route to enable further noise suppression. Our scheme opens the way to quantum demonstrations using a broadband memory, significantly advancing the search for scalable quantum photonic networks.